1993
DOI: 10.1128/aem.59.11.3686-3694.1993
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth and activity and modes of penetration of Escherichia coli in unconsolidated porous materials

Abstract: Statistically reliable data on the in situ rates of growth, substrate consumption, and product formation are required to test the validity of the mathematical models developed for microbially enhanced oil recovery and in situ bioremediation processes. A simple, replicable porous-core system that could be aseptically divided into sections at various times was developed to follow the kinetics of microbial growth and metabolism in situ. This core system was used to study the kinetics of growth and the mode of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…The aqueous biomass was significantly attenuated within the pulse interior. Biological processes that could lead to this reduction in aqueous biomass include a reduction in growth in the pulse interior due to oxygen limitations [Jenneman et al, 1985[Jenneman et al, , 1986Reynolds et al, 1989;Sharma et al, 1993] Figure 5c was almost identical to the experimental data, suggesting that the suppression of the electrostatic potential was the dominant process resulting in the decrease in aqueous biomass within the pulse interior.…”
Section: Pre-experimental Modeling Of the Flow Cell Design Showed Thasupporting
confidence: 62%
“…The aqueous biomass was significantly attenuated within the pulse interior. Biological processes that could lead to this reduction in aqueous biomass include a reduction in growth in the pulse interior due to oxygen limitations [Jenneman et al, 1985[Jenneman et al, , 1986Reynolds et al, 1989;Sharma et al, 1993] Figure 5c was almost identical to the experimental data, suggesting that the suppression of the electrostatic potential was the dominant process resulting in the decrease in aqueous biomass within the pulse interior.…”
Section: Pre-experimental Modeling Of the Flow Cell Design Showed Thasupporting
confidence: 62%
“…With growing interest surrounding in situ bioremediation as a treatment option for cleaning up contaminated soil, a few experimental studies (18,22,25,26) have been aimed at determining rates of bacterial penetration through porous media. These studies have typically involved measurement of rates, in units of distance per time, which differ depending on the type of soil (physical characteristics and porosity) used.…”
Section: Discussionmentioning
confidence: 99%
“…López de Victoria (18) studied several subsurface isolates and their chemotactic response toward and/or away from trichloroethylene and noted rate enhancements from 10 m/s to 20 m/s for several strains when a trichloroethylene gradient was established within 30-cm columns filled with topsoil. Sharma et al (26) improved upon this method of determining penetration rates of E. coli by sectioning columns at a given incubation time and determining bacterial density profiles throughout the column. This group concluded that a nonchemotactic E. coli mutant penetrated in a diffusive manner at a faster rate than its chemotactic parent.…”
Section: Discussionmentioning
confidence: 99%
“…The authors postulate that the universal microorganisms thriving in all the sampling points have the capacity to give an ecophysiological response to variational habitats in a broad or specific way. Microorganisms, especially the rhizospheric ones, have the potential to alter the properties of the soil with cells or cellular secretions (Degans, 1997;Jing et al, 2007;Sharma et al, 1993). Multiple secondary effects resulted from microbial consumption and production of metabolites, which may influence the solids, water, and atmosphere of given soil environments (Lehman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%